2019
DOI: 10.1002/spy2.48
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal mobile keystroke dynamics biometrics combining fixed and variable passwords

Abstract: Recent works have demonstrated the possibility to craft successful statistical attacks against keystroke dynamic biometric password. Those attacks leverage the possibility to capture several keystroke dynamics samples for a given password string, and then extract and use their distributional properties to craft the attack. These approaches are by design more likely to be successful when launched against fixed passwords, as several samples of the passwords can be captured through successive login sessions. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As mobile systems advance, more features related to keystroke biometrics trait are extracted. Button touching pressure and button touching area are factors that differentiate users besides temporal and spatial features [28][29][30][31]. In one study that fused temporal features, finger area, and finger pressure, an EER of 2.3% was achieved [31].…”
Section: Related Workmentioning
confidence: 99%
“…As mobile systems advance, more features related to keystroke biometrics trait are extracted. Button touching pressure and button touching area are factors that differentiate users besides temporal and spatial features [28][29][30][31]. In one study that fused temporal features, finger area, and finger pressure, an EER of 2.3% was achieved [31].…”
Section: Related Workmentioning
confidence: 99%
“…Our classification of adversary models in mobile device authentication is related to the ISO/IEC 62443 security levels that have been specified in ISA99 [131] 10 : SL0 "No special requirement or protection required" SL1 "Protection against unintentional or accidental misuse" 9 Changes in electromagnetic signals at a radio receiver caused by movement of a user or object reflecting the signals are visible in the CSI. 10 Only a summary document of this standard is available online at the time of this writing, in the form of public slides by Pierre Cobes; Available online at http://isa99.isa.org/Public/Meetings/Committee/201205-Gaithersburg/ISA-99-Security_ Levels_Proposal.pdf. In this article, we use the slightly more detailed wording from https://en.wikipedia.org/wiki/IEC_ 62443.…”
Section: Classifying Adversary Models In Mobile Device Authenticationmentioning
confidence: 99%
“…Image-based authentication has an advantage [261,292] over password or PIN-based authentication due to improved usability [293], and since it is easier to recognize or recall an image than a text [62,73]. However, memorability and security strength of image-based recognition in comparison to PIN and password based solutions when multiple (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of such passwords need to be remembered, has not been considered in the literature. Davis et al [61] further found that (1) user password selection is biased by race and gender [39], thus lowering password entropy, (2) the need for several rounds to provide a reasonably large password space impairs usability, and (3) recognition-based systems are vulnerable to replay attacks [15,266].…”
Section: Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Standard machine learning approaches have been used in most of the studies performing closed‐set verification on KD data acquired when typing free text on mobile devices. Specifically, RF has guaranteed the best recognition rates in [52, 55], while CART have been used together with LR in [11]. SVMs with Gaussian kernels have been employed in [56], and also neural networks have been exploited, as in [54, 61].…”
Section: Template Comparison and Decision Makingmentioning
confidence: 99%